PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK MODELING SIMBOLIK UNTUK MENINGKATKAN PERILAKU PROSOSIAL PADA SISWA KELAS VIII MTs NEGERI 01 LEBONG - Almunawarah, Liza; Hadiwinarto; Sinthia, Rita (UNIVERSITAS BENGKULU, 2023)
This study purposed to describe the effect of group guidance service with symbolic modeling techniques to improve prosocial behavior of student class VIII MTs Negeri 01 Lebong. The method in this study used an experiment with a one group prestest-posttest design. The population in this studi were all student of class VIII A MTs Negeri 01 Lebong totaling 30 students with the research sample consist of 10 students. The sample were taken by random sampling technique. The data collection using a questionnare with a Likert scale model. Data analysis technique was using the t test (paired sample test). The result of the hypothesis test obtained in this study showed that the value of t = -5.361 and sig (2-tailed) 0.000 means that there is a significant influence on group guidance service with symbolic modeling techniques to improve students prosocial behavior Keyword : prosocial behavior, group guidance, symbolic modeling techniques